Ornithine α-Ketoglutarate Alleviates Inflammation via Regulating Ileal Mucosa Microbiota and Metabolites in Enterotoxigenic Escherichia coli-Infected Pigs - Li, Yuying; Bao, Xuetai; Yang, Fan; Tian, Junquan; Su, Wenxuan; Yin, Jie; Yao, Kang; Li, Tiejun; Yin, Yulong (Frontiers in Nutrition, 2022)
Enterotoxigenic Escherichia coli (ETEC) is the one of the main caused of diarrhea in weaned piglets and ornithine α-ketoglutarate (OKG), as a food supplement, has been shown to improve intestinal immune status in animals and humans. However, it is remain unknown about the OKG alleviating inflammation through regulation gut microbiota and its metabolites on ETEC-infected piglets. This study was conducted to explore the impact of OKG on growth performance, immunity, and ileal mucosa microbiota, and its metabolites of piglets infected with ETEC. A total of 40 pigs were performed using a 2 × 2 factor design; the major factors were diet (basal diet or 1% OKG diet) and challenge ( Escherichia coli or LB Broth). The results showed that ETEC-infection inhibited growth performance and OKG supplementation alleviated growth performance. Interestingly, ETEC-infection increased the serum TNF-α, and IL-6, and decreased the serum IL-10, downregulated the mRNA expression of IL-1β, IL-6, MyD88, and improved the mRNA expression of IL-8, IL-18 and TLR4. OKG inhibited serum IL-6, and suppressed the phosphorylation of downstream signals of NF-κB/JNK in ileum, and enhanced serum IL-10 and ileum SIgA in ETEC-challenged piglets. OKG supplementation enhanced the mRNA expression of IL-1β, IL-10 and reduced NF-κB and MyD88 in the ileum. Importantly, OKG reversed intestinal microbiota dysfunction, including the diversity of ileal microbiota, the relative abundances of Actinobacillus, Turicibacter and [Acetivibrio]_ethanolgignens_group, which significantly affected arachidonic acid metabolism and primary bile acid biosynthesis. Collectively, our results suggest that OKG improves growth performance, regulates immunity, and ileal mucosa microbiota and metabolites in ETEC-infection piglets.